Pengaruh Pengetahuan Investasi, Persepsi Risiko, Return, dan Motivasi pada Minat Mahasiswa Berinvestasi Cryptocurrency - Kadek Diah Listiyani Putri; I Gusti Ayu Nyoman Budiasih (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The Ministry of Finance shows data regarding interest in investing in Cryptocurrency in Indonesia continues to increase. This study aims to obtain empirical evidence of the influence of investment knowledge, risk perception, returns, and motivation on students' interest in investing in Cryptocurrency. The sample was taken using the purposive sampling method and obtained 110 student respondents for the 2019 and 2020 batches of the Bachelor of Accounting study program, Faculty of Economics and Business, Udayana University. Multiple linear regression analysis was used in this study as a data analysis technique. Based on the results of the analysis, it was found that things related to investment knowledge, returns, and motivation had a positive effect on students' interest in investing in Cryptocurrency, while perceptions of risk had no effect on students' interest in investing in Cryptocurrency.